DESIGN AND DEVELOPMENT OF A FISH SLICING MACHINE FOR A CHIP PRODUCTION ON TOMOY ISLAND - M Jabbar Sadik (Universitas Riau Kepulauan, 2025)
The production process of fish chips begins with the slicing of fish as the raw material. To improve efficiency and consistency in fish chip production, a slicing machine is needed that can produce fish slices with uniform thickness and good quality. This study aims to design and build a fish processing slicing machine with adjustable parameters to meet the needs of small to medium-sized industries. The designed machine includes main components such as a cutting blade, a drive motor, and a slice thickness adjustment system. The machine prototype was tested to ensure its effectiveness in producing fish slices that meet quality standards. The test results showed that the built machine could improve production efficiency and slice quality, as well as reduce reliance on human labor.